Efektifitas Kebijakan Program Adiwiyata Dalam Mencetak Generasi Penerus Bangsa Peduli Lingkungan Di Indonesia - Dinarjati Eka Puspitasari (Batulis Civil Law Review, 2021)
Adiwiyata Program is a program implemented by the State Ministry of Environment and Forestry to create schools that care and have an environmental culture. This program aims to save and preserve the environment for the benefit of future generations, followed by schools from elementary to secondary levels. Adiwiyata program is expected to produce students who are young generations to care for the environment. This research aims to examine the need to promote adiwiyata program policies in creating the next generation who cares about the environment throughout Indonesia; the effectiveness of Adiwiyata program policies in creating the nation's next generation; the need for a role from the Government related to Adiwiyata program policies in creating the next generation of the nation who cares about the environment in Indonesia. This research is a normative legal research. The research materials are taken from literature study. Qualitative descriptive approach is employed to analyse the materials. This research generates some results: 1) Adiwiyata program policies in creating the nation's next generation who care about the environment need to be encouraged in schools throughout Indonesia, because it is positive for the development of the nation's next generation in an effort to preserve environmental functions, to create a good and healthy living environment; 2) Adiwiyata program policy has been running effectively, although it has not been optimal in creating the nation's next generation; 3) The role of the Government is needed in relation to the Adiwiyata program policy in creating the next generation who cares about the environment in Indonesia, to provide environmental awareness for citizens